Bhutan's Integration with the Global Economy : International Investment Treaties and Conventions - World Bank (World Bank, Washington, DC, 2019)
In this context, Bhutan can become wealthier through accelerating both domestic and foreign investment, as well as signing investment treaties. These investments could provide not just capital but also bring necessary skills, knowledge and ideas, and help the country move beyond hydropower. Today FDI inflows are small and constrained, on the one hand, by regulatory barriers and insufficient investment promotion, and, on the other, by inadequacies in skills and infrastructure. Bhutan can benefit from the experience of East Asia and other countries on how to break out of this low investment trap. FDI can help the macroeconomic balance by increasing exports and reducing the current account deficit, although it is not clear the future impact on growth, since it will depend on the quality and type of FDI inflows. FDI can also help create trade. Theoretically, firms invest abroad to expand their sales markets when trade costs are too high, therefore FDI is a substitute for trade. FDI in non-tradable sectors (services, etc) has this feature. However, in practice, FDI goes to export-oriented sectors including extractives but also manufacturing. Given the landlocked nature of geographic setting of Bhutan (with higher trade cost than countries such as India or Bangladesh), FDI could go primarily to non-tradable (at least as shown in the recent trend in the greenfield FDI). In this context, it will be important to use FDI to tap into regional value chains.